All-oral low-dose chemotherapy TEPIP is effective and well-tolerated in patients with peripheral T-cell lymphoma - Fante, Matthias A.; Harrer, Dennis C.; Zartner, Barbara; Lüke, Florian; Mayer, Stephanie; Menhart, Karin; Reichle, Albrecht; Herr, Wolfgang; Vogelhuber, Martin; Heudobler, Daniel (Frontiers in Oncology, 2023)
Purpose: Peripheral T cell lymphoma (PTCL) is a rare and heterogenous hematologic malignancy with poor prognosis especially in elderly and frail patients not being eligible for intensive treatment. The resulting palliative setting necessitates tolerable but effective schedules for out-patient treatment. TEPIP is a locally developed, all-oral low-dose regimen comprising trofosfamide, etoposide, procarbazine, idarubicin and prednisolone. Methods: In this observational retrospective single-center study safety and efficacy of TEPIP was evaluated in 12 patients (pts.) with PTCL treated at the University Medical Center Regensburg between 2010 and 2022. End points were overall response rate (ORR) and overall survival (OS), and adverse events were individually reported according to the CTCAE criteria. Results: The enrolled cohort was characterized by advanced age (median 70 years), extensive disease (100% AnnArbor ≥ stage 3) and poor prognosis (75% high/high intermediated international prognostic index). Most common subtype was angioimmunoblastic T cell lymphoma (8/12) and 11/12 patients had relapsed or refractory disease at TEPIP onset with a median of 1.5 prior treatment regimens. After a median of 2.5 TEPIP cycles (total 83 cycles) ORR was 42% (complete remission 25%) and OS reached a median of 185 days. Any grade of adverse event (AE) occurred in 8/12 patients with 4 patients showing AE ≥ CTCAE grade 3 (33%) and AEs were mainly non-hematological. Conclusion: TEPIP demonstrated competitive efficacy with a tolerable safety profile in a highly palliative cohort of patients with difficult-to-treat PTCL. The all-oral application, which makes outpatient treatment possible, is particularly noteworthy.